Pengaruh Value Co-Creation Terhadap Keterlibatan Merek dan Niat Pembelian: Studi Kasus Menantea: The Effect of Value Co-Creation On Brand Engagement and Purchase Intention: A Case Study of Menantea - Felicia Candra; Nathasya Tirtoatmodjo; Regina Jokom (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Menantea is selling tea-based drinks and has managed to reach more than 200.000 followers on Instagram in the first 5 days of its opening. This research was conducted to determine the impact of value co-creation (dialogue, access, risk-benefit, and transparency) on Menantea Instagram followers’ brand engagement and purchase intention. This research involves 114 respondents who followed @menantea.toko Instagram account. This research used Partial Least Square (PLS) data analysis techniques. The results showed that value co-creation delivered by Menantea had a positive and significant effect on brand engagement. Moreover, brand engagement had a positive and significant effect on purchase intention, and value co-creation had a positive and significant effect on purchase intention. Therefore, value co-creation had a positive and significant effect on purchase intention with brand engagement as a mediating variable. Brand engagement acts as a partial mediation that strengthens the effect of value co-creation on purchase intention in Menantea. Keywords: brand engagement, instagram, purchase intention, value co-creation, menantea